A single-centered study of factors affecting colistin related nephropathy - Çakmak, Güzin; Abidin Öztürk, Zeynel (International Journal of Medicine, 2020)
Background: Colistin is an old antibiotic and used for resistant gram-negative infections. Nephrotoxicity is the most common side effect and restricts clinicians to use it. Many risk factors suggested for the development of nephropathy. It could be better to know risks to prevent nephropathy development. Objectives: In this study, we aimed to evaluate factors that affecting the development of nephropathy in patients who were hospitalized in hematology, oncology, palliative care, and intensive care units. Methods: 125 patients aged 20-93 years old were enrolled in this retrospective study. Data were obtained from the pharmacy of the university hospital and information management system of the hospital. Results: Among 125 patients included in the study, 15 developed KDIGO stage 1 nephropathy, 21 stages two nephropathies, and four stages three nephropathies, respectively. Age, albumin level, and bilirubin levels were shown to be related to nephropathy. We found the cut off value of albumin 3.05 mg/dl for development of nephropathy (sensitivity 70%; specificity 66%; CI=95%, p=0.003) and mortality (sensitivity 69%; specificity 61%; CI=95%, p<0.001). We revealed that age and bilirubin levels independently affected the development of nephropathy in linear regression analysis (r2 =0.131, p=0.032; p=0.015). Also, mortality was denoted to be related to albumin and bilirubin levels independently in linear regression analysis (r2 =0.161, p=0.03; p=0.004). Conclusions: Older age, hypoalbuminemia, and hyperbilirubinemia were risk factors for colistin related nephropathy and mortality. Further studies will be better to elucidate relationships more clearly. Â Â Â